2007
DOI: 10.1107/s1600536807047198
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen bis(tetraphenylimidodiphospinic acid) triiodide

Abstract: Key indicators: single-crystal X-ray study; T = 297 K; mean (C-C) = 0.009 Å; R factor = 0.053; wR factor = 0.120; data-to-parameter ratio = 15.5. organic compounds o4206 # 2007 International Union of Crystallography

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…11. Among these data, three are obtained from two cation-anion compounds [FAQREV (Hagenbach et al, 2004) and WINLEL (Copolovici et al, 2007)], which are shown as red parts in the Fig. 11.…”
Section: (C) 2 P(o)(n) Structuresmentioning
confidence: 99%
“…11. Among these data, three are obtained from two cation-anion compounds [FAQREV (Hagenbach et al, 2004) and WINLEL (Copolovici et al, 2007)], which are shown as red parts in the Fig. 11.…”
Section: (C) 2 P(o)(n) Structuresmentioning
confidence: 99%